Evaluation of the effect of defects on the mechanical performance of components manufactured by selective laser melting - Leuders, S.; Tröster, Thomas; Brenne, F.; Riemer, A.; Richard, H. A.; Niendorf, T.

On the mechanical performance of structures manufactured by selective laser melting: Damage initiation and propagation - Leuders, S.; Tröster, Thomas; Riemer, A.; Richard, H. A.; Niendorf, T.

Reliable communication using Erasure Codes for monitoring bats in the wild - Mutschlechner, Margit; Klingler, Florian; Erlacher, Felix; Hagenauer, Florian; Kiessling, Marcel; Dressler, Falko (2014 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

On the impact of street width on 5.9 GHz radio signal propagation in vehicular networks - Erlacher, Felix; Klingler, Florian; Sommer, Christoph; Dressler, Falko (2014 11th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

Fast Collisionless Pattern Formation by Anonymous, Position-Aware Robots - Lukovszki, Tamás; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Continuous Aggregation in Dynamic Ad-Hoc Networks - Abshoff, Sebastian; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

Time-causal material modeling in the simulation of guided waves in circular viscoelastic waveguides - Bause, Fabian; Schroder, Andreas; Rautenberg, Jens; Henning, Bernd; Gravenkamp, Hauke (2014 IEEE International Ultrasonics Symposium)

Unsicherheitsanalyse eines Vorwärtsmodells zur Simulation transienter Wellenausbreitung im Hohlzylinder - Bause, Fabian; Weber, Daniel; Rautenberg, Jens; Henning, Bernd

Model based sensitivity analysis of Leaky-Lamb wave propagation to the variation of viscous lubricant properties - Bause, Fabian; Brückner, Christoph; Miedl, Jens; Henning, Bernd (Beiträge der 17. ITG/GMA-Fachtagung)

Modellgestützte Analyse des Trocknungsverhaltens von Dispersionslacken aus Daten einer NIR-Multidetektoranordnung - Hoof, Christian; Appelhans, Silke; Henning, Bernd
Zur schnellen und berührungslosen Materialfeuchtebestimmung wird unter anderem die Infrarotreflexionsmessung ge-nutzt. In dieser Untersuchung wird das Trocknungsverhalten von Dispersionslack auf einem rauen Substrat mit einer Multidetektoranordnung untersucht. Durch diese Anordnung ist es möglich, gerichtete und diffuse Strahlungsanteile zu detektieren, wodurch zeitvariable Glanzeffekte an der Lackoberfläche miterfasst werden. Mit Hilfe eines Raytracing-Algorithmus wird die Trocknung eines Dispersionslackes simuliert und anhand von Messdaten mit einem FTIR-Spekt-rometer verifiziert.

Sensitivitätssteigerung im Rahmen eines inversen Ansatzes zur Materialparameterbestimmung für Piezokeramiken durch Elektrodenmodifikationen - Unverzagt, Carsten; Henning, Bernd
Simulationen mittels der Finiten Element Methode (FEM) sind heute ein fester Bestandteil im Entwicklungsprozess von Ultraschallsystemen. Durch die simulative Ermittlung der transienten Schwingungsvorgänge können Optimierungen bezüglich gewünschter Zielkriterien vorgenommen werden. Hierdurch lassen sich die aufwendige Prototypenfertigung reduzieren und günstige Entwurfspunkte schneller ermitteln.

On the computation of dispersion curves for axisymmetric elastic waveguides using the Scaled Boundary Finite Element Method - Gravenkamp, Hauke; Bause, Fabian; Chongmin, Song (Computers and Structures)

SAT-Based ATPG beyond Stuck-at Fault Testing - Hellebrand, Sybille; Wunderlich, Hans-Joachim (DeGruyter Journal on Information Technology (it))

Adaptive Bayesian Diagnosis of Intermittent Faults - Rodriguez Gomez, Laura; Cook, Alejandro; Indlekofer, Thomas; Hellebrand, Sybille; Wunderlich, Hans-Joachim (Journal of Electronic Testing - Theory and Applications (JETTA))

Common Fate Graph Patterns in Monte Carlo Tree Search for Computer Go - Graf, Tobias; Platzner, Marco (2014 IEEE Conference on Computational Intelligence and Games)

Reducing the power consumption of household refrigerators through the integration of latent heat storage elements in wire-and-tube condensers - Sonnenrein, G.; Elsner, A.; Baumhögger, Elmar; Morbach, A.; Fieback, K.; Vrabec, J. (International Journal of Refrigeration)

Apparatus for the measurement of the speed of sound of ammonia up to high temperatures and pressures - Dubberke, Frithjof H.; Rasche, David B.; Baumhögger, Elmar; Vrabec, Jadran (Review of Scientific Instruments)

Prediction methods for pool boiling heat transfer: A state-of-the-art review - Gorenflo, Dieter; Baumhögger, Elmar; Herres, Gerhard; Kotthoff, Stephan (International Journal of Refrigeration)

Mixed methods analysis of enterprise social networks - Trier, Matthias; Behrendt, Sebastian; Richter, Alexander (Computer Networks)

Modeling and inverse identification of a high bandwidth ultrasonic measurement setup based on piezoelectric 1-3 composites - Bause, Fabian; Webersen, Manuel; Rautenberg, Jens; Henning, Bernd

Modellbasierte inverse Identifikation von Ultraschall-Transducern anhand der elektrischen Eingangsimpendanz - Bause, Fabian; Webersen, Manuel; Rautenberg, Jens; Henning, Bernd

Mixed methods analysis of enterprise social networks - Behrendt, Sebastian; Richter, Alexander; Trier, Matthias (Computer Networks)

Der richtige Ansprechpartner im dynamischen Interaktionsnetzwerk - Trier, Matthias; Müller, Matthias; Bobrik, Annette (HMD Praxis der Wirtschaftsinformatik)

MEDIA ENGINEERING WITH A CONTENT HUB SYSTEM. GENERIC CONTENT TRANSFORMATION FOR MOBILE MEDIA - Herzog, Michael; Trier, Matthias (International Journal of Computing)
A primary problem in multimedia content production is the plethora of formats and the resulting multiple point-to-point transformation processes in different content formatting specifications. However, these content transformation processes can be conceptually broken down into a limited set of abstract principles. This allows a unified approach that theoretically enables the transformation of any given input channel into any desired output. Based on this principle, the present article introduces the concept of Generic Content Transformation and the related project MOCCA, which develops the corresponding software implementation of generic content transformation for a variety of input and output channels. To balance technical similarities with specific properties of different media channels, we suggest a combination of an XML-based structure (MocML) and a high level authoring environment. Generic Content Transformation further allows for novel means of accessing assets via compound search algorithms. In the second part we summarize and discuss current results and experiences in three scenarios of media production, including mobile media.
Keywords: Multimedia Authoring; Mobile Content; Cross Media Production; Content Engineering; Media Retrieval

Business Intelligence 2.0 - Behrendt, Sebastian; Richter, Alexander; Schäfer, Sebastian; Trier, Matthias (Vernetzte Organisation)

Towards a Conceptualization of Online Community Health - Wagner, David; Richter, Alexander; Trier, Matthias; Wagner, Heinz-Theo (Proceedings of the 35th International Conference on Information Systems. ICIS 2014)
Along with the increasing popularity of social media and online communities in many business settings, the notion of online community health has become a common means by which community managers judge the condition or state of their communities. It has also been introduced to the literature, yet the concept remains underspecified and fragmented. In this paper, we work toward a construct conceptualization of online community health. Through a review of extant literature and dialogue with specialists in the field, we develop a multi-dimensional construct of online community health, consisting of seven elements. In writing this paper, we attempt to foster theory development around new organizational forms by advancing a new and important construct. The paper further provides guidance to the managers of social media and online communities by taking a systematic look at the well-being of their communities.
Keywords: Social media; Online communities; Online community success; Online community health; Construct conceptualization

Modeling intrinsic defects in LiNbO3 within the Slater-Janak transition state model - Li, Yanlu; Sanna, Simone; Schmidt, Wolf Gero (The Journal of Chemical Physics)

Modeling LiNbO3 Surfaces at Ambient Conditions - Hölscher, Rebecca; Schmidt, Wolf Gero; Sanna, Simone (The Journal of Physical Chemistry C)

The set of circular flow numbers of regular graphs - Schubert, Michael; Steffen, Eckhard (J. Graph Theory)

Petersen colorings and some families of snarks - Hägglund, Jonas; Steffen, Eckhard (Ars Mathematica Contemporanea)

PAC Rank Elicitation through Adaptive Sampling of Stochastic Pairwise Preferences - Busa-Fekete, Robert; Szörényi, B.; Hüllermeier, Eyke (Proceedings AAAI 2014, Quebec, Canada)

A Survey of Preference-Based Online Learning with Bandit Algorithms - Busa-Fekete, Robert; Hüllermeier, Eyke (Proceedings Int. Conf. on Algorithmic Learning Theory (ALT), Bled, Slovenia)

Mining Rank Data - Henzgen, Sascha; Hüllermeier, Eyke (Proceedings Discovery Science, Bled,Slovenia)

The Choquet kernel for monotone data - Fallah Tehrani, A.; Strickert, M.; Hüllermeier, Eyke (Proceedings ESANN , Bruges, Belgium)

Learning Solution Similarity in Preference-Based CBR - Abdel-Aziz, A.; Strickert, M.; Hüllermeier, Eyke (Proceedings Int. Conf. Case-Based Reasoning (ICCBR), Cork, Ireland)

Dyad Ranking Using A Bilinear Plackett-Luce Model - Schäfer, Dirk; Hüllermeier, Eyke (Proceedings Lernen-Wissensentdeckung-Adaptivität (LWA), Aachen, Germany)

Machine Learning and Knowledge Discovery in Databases-European Conf. ECML/PKDD, Nancy, France - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Proceedings, Parts I-III. Lecture Notes in Computer Science)

On Consumer Purchasing Behavior in Electronic Markets - Herrmann, Philipp

Preference Learning (Dagstuhl Seminar 14101) Dagstuhl Reports - Fürnkranz, J.; Hüllermeier, Eyke; Rudin, Cynthia; Slowinski, Roman; Sanner, Scott

Survival analysis on data streams: Analyzing temporal events in dynamically changing environments - Shaker, Ammar; Hüllermeier, Eyke (Applied Mathematics and Computer Science)

Ausgewählte Beiträge des GMA-Fachausschusses 5.14 - Hoffmann, F.; Hüllermeier, Eyke; Kroll, A. (Computational Intelligence Automatisierungstechnik)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Data Min. Knowledge Discovery)

Visualization of evolving fuzzy rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (Evolving Systems)

Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Rejoinder on "Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Correlation-based embedding of pairwise score data - Strickert, M.; Bunte, K.; Schleif, F.- M.; Hüllermeier, Eyke (Neurocomputing)

Reliable classification: Learning classifiers that distinguish aleatoric and epistemic uncertainty - Senge, Robin; Bösner, S.; Dembczynski, K.; Haasenritter, J.; Hirsch, O.; Donner-Banzhoff, N.; Hüllermeier, Eyke (Information Sciences)

Protein Sub-Cellular Localization Prediction for Special compartments via Optimized Time Series Distances - Mernberger, M.; Moog, M.; Stork, S.; Zauner, S.; Maier, U.G.; Hüllermeier, Eyke (J. Bioinformatics and Computational Biology)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Machine Learning)

Preference-Based Reinforcement Learning: evolutionary direct policy search using a preference-based racing algorithm - Busa-Fekete, Robert; Szörényi, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (Machine Learning)